Endofity – charakterystyka i możliwości wykorzystania w leśnictwie - Hilszczańska, Dorota (Leśne Prace Badawcze, 2016)
Endophytes are organisms that live within the plant tissue without usually causing any symptoms. In plants of natural ecosystems, endophytic fungi are in fact ubiquitous. This review summarizes research carried out on their biology emphasizing their functionality in terms of the host range, the colonization extent, the way of transmission between hosts and their influence on host fitness. The main focus will be on two classes of fungal endophytes, class 2 and 4 (Dark Septate Fungi), due to their potential for practical application in forestry. Raising awareness of the potential of endophytes to enhance the host’s resistance to pathogens, insects and anthropogenic disturbances is a key factor in developing applications for forest management.